As metamorfoses da coisa: modos de apresentação do real nos escritos de Primo Levi - Luciola Freitas de Macedo (2014)
This research aims to present and clarify, based on the notion of Thing as conceptualized by Jacques Lacan, on the heels of Sigmund Freud, the different ways in which Primo Levi, chemist, writer and an Auschwitz survivor, has used writing as a way to face the Nazi thing ", the trauma of deportation and confinement and what continues to traumatize even after the liberation of the concentration camps in January 1945. For this purpose, we will examine several dimensions of his work: testimony, poetry, short story, essay, articles in newspapers and interviews given throughout his life. First, we discuss the concept of Thing and the problem of truth by examining his fantastic tales, and, above all, the notion of gray zone, central axis on which constitutes his book, The drowned and the saved. Second, we chose to investigate the concept of the Thing in the teachings of Jacques Lacan. The next step examines how, in face of the Thing and of the inassimilable of the real trauma, the writer uses his poetic writing. Finally, we follow the metamorphosis of the Thing in If this is a man, his first testimony, and as from his trajectory as a writer, through the use of oxymoron, until the genesis of the original concept of "gray zone".